Keberlanjutan Permukiman Rawa Desa Baru di Kabupaten Hulu Sungai Utara Kalimantan Selatan - Chaidir, Ahmad; Murtini, Titien Woro (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
As the traditional village, Desa Baru has a value and local wisdom which is represented by spatial planning and environmental management. In terms of environmental management, the social behavior of local people in Desa Baru strengthens the existence of resided activity. However, the resided activity in Desa Baru conducted by local people can't be revealed as sustainable activity unless an assessment of sustainability has been conducted. Thus, the researcher is eager to examine the sustainability of swamp settlement area in Desa Baru: